Local self-government as a factor of formation of the civil society in the ukraine: historical experience, modernity, perspectives - Бакуменко, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The role of local self-government in the process of formation of the civil society in Ukraine are discussed. The author analyzes the historical experience of local self-government as a factor of formation of civil society, the value of local self-government in the processes of development of civil society in modernity is probed, the prospects of development of the local self-government in Ukraine are determined.